La ética del profesional en turismo. Servicio hotelero innovador y sostenible - Nohemy Josefina Moya (Études Caribéennes)
This article aims, assess the ethical conduct of professional tourism as an element incident innovative and sustainable tourism service. It is a critical analysis since it constructive relationship of theory and practice, of what is and what ought to be the executions of tourism professionals is given. For your approach proceeded to a desk study, based on a literature review of current on the subject matter material concluding that all tourism innovation, from identification and conversion of resource to its value as a tourism product requires a tourist information system, a technology. Furthermore sustainable tourism is a strategy that promotes the development of communities Scenic, cultural, environmental wealth, etc. The practice of professional ethics in tourism is crucial to the quality of service and innovative Hotelier this measure helps to make it sustainable over time.